The Christian mystery : from pagan myth to Christian mysticism - Bouyer, Louis, 1913-2004 (T & T Clark International, 2004)
One of the most gifted and internationally renowned theologians of our time here explores the importance of mystery and mysticism in the Christian tradition. He begins with a historical look at myth and mystery in pagan, Hellenistic and Classical cults, and the subsequent development in Christian mysticism and spirituality. From myth and mystery he moved to mysticism in the Christian West up to the present. Christian tradition is compared to Jewish, Islamic and Buddhist mystic experiences. Throughout, Bouyer seeks to focus on the power and meaning of these phenomena in their place in the moder.